Load balancing optimization of capacitated networks with path protection - Sousa, A. de
This article deals with the routing of a given set of traffic flows over a telecommunications network with given link capacities. The aim is to optimize the network load balancing. We address the case where each traffic flow is supported by two edge disjoint routing paths, a mechanism known as path protection, which guarantees full traffic protection of single link failures. We describe an exact solving method based on mathematical programming and propose a meta-heuristic algorithm. Then, we define a set of case studies arising in the context of metropolitan Ethernet networks. Finally, we present the computational results of both methods and compare them in terms of solutions optimality versus runtime.